Review on nutritional, medicinal and pharmacological properties of Guava (PSIDIUM GUAJAVA LINN.) - BABY JOSEPH; MINI PRIYA R (International Journal of Pharma and Bio Sciences, 2010)
Guava (Psidium guajava Linn.) commonly known for its food and nutritional values throughout the world. The medicinal properties of guava fruit, leaf and other parts of the plant are also well known in traditional system of medicine. Since, each part of guava tree possesses economic value; it is grown on commercial scale. Guava plant is considerable process has been achieved regarding the biological activity and medicinal application of guava and the fruit considered as poor man apple of tropics. The guava plant parts are used for the development of various industrial and pharmaceutical products. In the present review, nutritional value of guava fruit and medicinal properties its various parts have been discussed to provide collective information on its multi purpose commercial values.